Good agricultural practices (GAP) to improve rice productivity in Tanzania - CGIAR Research Program on Rice (2021)
The GAP component technologies have been tested in Kilombero and Kahama regions of Tanzania. GAP components are land preparation, cultivar choice, nursery sowing, line planting, weeding and fertilizer application. Yield increased from 1.2 - 2.2 to 3.2 – 4.5 t/ha. More than 2000 farmers trained on GAP in Tanzania.